2006
DOI: 10.1149/1.2193071
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectrode Ensembles Using Carbon Nanopipettes

Abstract: We demonstrate a simple approach for fabricating nanoelectrode ensembles ͑NEEs͒ for nanostructures exhibiting conical morphologies. The fabrication concept utilizes the tapered geometries of carbon nanopipettes ͑CNPs͒ and entails one simple, dipcoating step with an insulating polymer to engineer their spatial distribution. After dip-coating, the CNPs in the NEE are separated by several micrometers. Uncoated CNP arrays exhibit peak-shaped behavior in cyclic voltammetry, whereas polymer-coated NEEs yield steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This peak is not present in the subsequent cycles. The half-sigmoidal shape of the CVs indicates a nanoelectrode-like behavior with a steady-state current [22]. This behavior suggests that the diffusion profiles for each Pd/Fe nanodomain do not overlap each other, as a consequence of their proper distribution that is provided inherently by the PC membrane.…”
Section: Characterization Studiesmentioning
confidence: 88%
“…This peak is not present in the subsequent cycles. The half-sigmoidal shape of the CVs indicates a nanoelectrode-like behavior with a steady-state current [22]. This behavior suggests that the diffusion profiles for each Pd/Fe nanodomain do not overlap each other, as a consequence of their proper distribution that is provided inherently by the PC membrane.…”
Section: Characterization Studiesmentioning
confidence: 88%
“…Using a SEKI model AX5200S-ECR MWCVD reactor, some other experiments were conducted on CNP array-coated platinum wire substrates using ECR plasma at pressures ranging from 50-100 mTorr with methane composition ranging from 0-5% CH 4 in H 2 using 500 Watts of MW power and Full Paper …”
Section: Methodsmentioning
confidence: 99%
“…[3] The CNP arrays, due to the conical geometry of the individual structures, could easily be made into nanoelectrode ensembles. [4] Furthermore, the conical structures could serve as good templates for producing nanodiamond tip arrays, which could be made into diamond nanoelectrode ensembles easily by the simple polymer-masking technique described in our earlier work. [4] Also, the nanodiamond tip arrays could find interest in functionalized biosensor [5] and field emission [6] applications.…”
Section: Introductionmentioning
confidence: 99%
“…53 In a method analogous to the insulated fiber optic tips, Lowe et al showed that an ensemble of conical CNTs grown on a Pt electrode could be partially insulated to create a NEE as demonstrated by sigmoidal CV traces showing steady-state diffusion, a characteristic of NEEs. 54 Very high density ensembles, characterized by their bulk addressability, have proven useful in electroanalytical chemistry, especially for the measurement of DNA hybridization. Inspired by the diffusion properties of ever smaller microelectrodes, the template methods developed by Martin to create NEEs have led to numerous devices with improved S/B ratios and lower limits of detection.…”
Section: Applicationsmentioning
confidence: 99%